2016
DOI: 10.3389/fonc.2016.00227
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Pro-Lymphangiogenic Programs during Mammary Involution and Postpartum Breast Cancer

Abstract: Postpartum breast cancers are a highly metastatic subset of young women’s breast cancers defined as breast cancers diagnosed in the postpartum period or within 5 years of last child birth. Women diagnosed with postpartum breast cancer are nearly twice as likely to develop metastasis and to die from breast cancer when compared with nulliparous women. Additionally, epidemiological studies utilizing multiple cohorts also suggest that nearly half of all breast cancers in women aged <45 qualify as postpartum cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 136 publications
0
25
0
Order By: Relevance
“…The particularly higher mortality of these women has been hypothesized to be due to a tumor-promoting microenvironment in the postpartum/lactational, involuting breast. Evolving animal and human data support that mammary involution entails a proin-flammatory process including an active period of lymphatic growth and remodeling, with tumors demonstrating high peritumoral lymphatic vessel density, increased incidence of lymph node metastasis (12)(13)(14)(15), and possible enrichment of liver and brain metastasis in the postpartum period (16). In addition, epidemiologic data reveal that the molecular phenotype of PABC tends to be more aggressive.…”
Section: Young Patientsmentioning
confidence: 99%
“…The particularly higher mortality of these women has been hypothesized to be due to a tumor-promoting microenvironment in the postpartum/lactational, involuting breast. Evolving animal and human data support that mammary involution entails a proin-flammatory process including an active period of lymphatic growth and remodeling, with tumors demonstrating high peritumoral lymphatic vessel density, increased incidence of lymph node metastasis (12)(13)(14)(15), and possible enrichment of liver and brain metastasis in the postpartum period (16). In addition, epidemiologic data reveal that the molecular phenotype of PABC tends to be more aggressive.…”
Section: Young Patientsmentioning
confidence: 99%
“…The few studies that have been carried out on mammary gland blood and lymphatic vasculature have shown that both vessel types are closely apposed to the mammary ducts with the former also penetrating the alveolar buds while the lymphatic network does not . Neolymphangiogenesis has been shown to occur during involution of the mammary gland in concert with upregulation of VEGF‐C, VEGF‐D and their receptors . A recent study showed that the GPI‐anchored membrane glycoprotein semaphorin 7A (SEMA7A) is expressed in the mammary epithelium during involution and suggested that SEMA7A may play a role in macrophage‐mediated lymphangiogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…17 The reason for this inconsistency can be contributed to the definition of the control group as all young women with breast cancer that are diagnosed after 1 year of childbirth, while it has been shown that the poor prognosis associated with a postpartum diagnosis can last up to 10 years. [4][5][6] In this review we will explore whether postpartum breast cancer, defined as breast cancer diagnosed up to 5 to 10 years in women<45 years of age, can be seen as a distinct entity with a unique biology. We will focus on the mechanisms that underly the poor prognosis of postpartum breast cancer, especially those related to mammary gland involution (regression of the mammary gland to its pre-pregnant state).…”
Section: Reviewmentioning
confidence: 99%
“…3 By this definition, postpartum breast cancer is estimated to represent 50% of breast cancers arising in young mothers within 10 years of their last childbirth. [4][5][6] Age at diagnosis, parity status, and breastfeeding history are among the most important risk factors for postpartum breast cancer. Older age at first birth correlates with an increased risk for postpartum breast cancer.…”
mentioning
confidence: 99%